A METHODOLOGICAL MODEL FOR DEVELOPING PHRASEOLOGICAL COMPETENCE (on the example of students majoring in Karakalpak language and literature) - Nurimbetova, Sarbinaz Keunimjaevna (SCIENCE and SOCIETY, 2026)
The article, an author's methodological model was developed that serves to improve and develop phraseological competence in philology students. The linguistic and cultural significance of phraseological units was revealed, and their teaching was based on a set of competence, cognitive, and communicative approaches. During the research, the components of phraseological competence were identified, and the mechanisms for their gradual development were identified. The proposed model is aimed at ensuring the continuous connection between the practical application of theoretical knowledge by philology students.
Keywords: phraseological competence; philology students; methodological model; phraseology; competency-based approach